Neurophysiology symptoms and vibration perception thresholds in young vibration-exposed workers - A follow-up study - Gerhardsson, Lars; Burström, Lage; Hagberg, Mats; Lundström, Ronnie; Nilsson, Tohr (Canadian Acoustics, 2011)
The development of neumphysiologic symptoms and vibration perception thresholds in a cohort of young vibration-exposed workers was studied. The follow-up study in 2006/2007 comprised 108 young male vibration-exposed workers from the machine shop and construction industries, who had been followed since they finished school. Measurements of vibrotactile thresholds were performed by delivering sinusoidal vibrations to the pulp of digits II and V, bilaterally, and registering the subjects response, using the HVLab Tactile Vibmmetcr system. A multiple regression analysis showed the strongest associations for the models including two of five calculated doses in the highest exposed quartile. The vibration perception thresholds are found to be at the same level at baseline and follow-up and no apparent deterioration is observed during the study period.